Modulating Territories, Penetrating Boundaries - MarkDavid Hosale; Chris Kievid (Footprint)
Drawing boundaries, defining territories: these are terms one could use to describe the activity of an architect. Architects can create constraints through the use of designed elements that help determine the flow of movement, perception, and usage of space. Boundaries imply the absence of flow, territories control the freedom of movement, and both imply a predetermined constraint. Conventionally a territory is conceived of as being fairly static, or at least moving slowly, on a historical scale through time. However, when the spaces in and around the building body can be programmed and driven, time-based morphology becomes a subject for architectural design.